Parent involvement in novice teen driving: a review of the literature - Simons‐Morton, B (BMJ Group, 2006)
Motor vehicle crashes remain elevated among novice teen drivers for at least several years after licensure. Licensing policies and driver education are the two primary countermeasures employed to decrease young driver crash risks. Graduated driver licensing policies have proved to be effective in reducing crash rates where evaluated. Driver education is an essential part of teaching teens the rules of the road and operating a vehicle, but requires few hours of professional driver training, relying mainly on parents to provide most of the supervised practice driving teens obtain before independent driving licensure. The few studies that have been conducted to increase parent supervised practice driving have not shown positive results. Moreover, it is unclear that increases in practice would improve independent driving safety. Recent research has shown that parent management of the early independent driving experience of novice teens improves safety outcomes, and other research has shown that it is possible to increase parent management practices. This paper provides a review of the literature on parent involvement in supervised practice and independent driving, and efforts to increase parental management.